2012
DOI: 10.1037/a0027973
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive predictors of academic achievement in young children 1 year after traumatic brain injury.

Abstract: Objective To examine cognitive predictors of academic achievement in young children with traumatic brain injury (TBI) and orthopedic injury (OI) shortly after injury and 1 year post-injury. Methods Participants included 3 to 6 year old children, 63 with TBI (46 with moderate TBI and 17 with severe TBI) and a comparison group of 80 children with OI. Academic achievement was assessed approximately 1 month and 12 months post injury, using three subtests from the Woodcock-Johnson Tests of Achievement-Third Editi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…In their cohort of children sustaining TBI between the ages of 3–12 years, Catroppa and colleagues (2009) found that subacute full scale IQ was positively associated with long-term reading accuracy, spelling, and arithmetic performance. In earlier follow-up of the participants in the current study, Fulton and colleagues (2012) found that subacute inhibitory control and verbal memory were positively associated with academic achievement scores at 1 year post injury. Associations of intellectual functioning and verbal memory with academic achievement are also reported in children who sustained their injuries in middle childhood (Catroppa & Anderson, 1999, 2007).…”
supporting
confidence: 48%
“…In their cohort of children sustaining TBI between the ages of 3–12 years, Catroppa and colleagues (2009) found that subacute full scale IQ was positively associated with long-term reading accuracy, spelling, and arithmetic performance. In earlier follow-up of the participants in the current study, Fulton and colleagues (2012) found that subacute inhibitory control and verbal memory were positively associated with academic achievement scores at 1 year post injury. Associations of intellectual functioning and verbal memory with academic achievement are also reported in children who sustained their injuries in middle childhood (Catroppa & Anderson, 1999, 2007).…”
supporting
confidence: 48%
“…The odds of unfavorable academic performance were 18 times higher for young children with TBI than for healthy comparison children 6 . In children ages 3 to 6 years at injury, severe TBI was associated with lower scores than moderate TBI and orthopedic injury groups on measures of applied mathematical reasoning and school readiness at both post-acute and 1 year follow-up evaluations 7, 8 .…”
Section: Time Since Injury Severity Of Tbi and Age At Injurymentioning
confidence: 86%
“…During the initial six months after TBI, core academic skills are commonly reduced in children with a wide range of injury severity. Difficulties have been reported in virtually all academic areas evaluated, including reading, mathematics, and written language in children with TBI as compared to children with orthopedic injuries or healthy children 68 . Although some initial improvement in core academic skills typically occurs during the first 6 to 12 months after injury, longitudinal studies indicate a persistent deficit in academic skills from one to five years post-injury 4, 5, 9 .…”
Section: Time Since Injury Severity Of Tbi and Age At Injurymentioning
confidence: 99%
“…Inhibitory control begins to develop early in childhood with adult-level performance on laboratory inhibition tasks typically achieved in late childhood or early adolescence (Bédard, Nichols, Barbosa, Schachar, Logan, & Tannock, 2002; Williams, Ponesse, Schachar, Logan, & Tannock, 1999). Evidence of associations between inhibition and academic outcomes exists but is fairly equivocal: whereas some studies have documented links to literacy and math achievement (see Allan, Hume, Allan, Farrington, & Lonigan, 2014 for recent meta-analysis; Blair & Razza, 2007; Bull & Scerif, 2001; Clark, Sheffield, Chevalier, Nelson, Wiebe, & Espy, 2013; Fulton, Yeates, Taylor, Walz, & Wade, 2012; Passolunghi & Siegel, 2004; St Clair-Thompson & Gathercole, 2006), others have failed to find significant correlations between inhibitory control processes and academic performance (e.g., Kim, Nordling, Yoon, Boldt, & Kochanska, 2013). …”
Section: Executive Functions: Structure Development and Associationmentioning
confidence: 99%